EFFECT OF SUCROSE AND 8-HQS ON VASE LIFE OF TWO CULTIVARS OF CARNATION Dianthus caryophyllus - M. M. Ibrahim (Mesopotamia Journal of Agriculture)
The experiment was carried out in Horticulture and Landscape design Dept. on two cultivars of carnation Plants Dianthus caryophyllus, Jeanne Dionis Blano white flowers and Marie Chabaud Jaune yellow flowers, to study the effect of pulse treatment(2h) with sucrose at 0, 5 and 10% interacted with 0, 300 and 600 mg/l of 8-hydroxyquinoline sulfate (8-HQS) in holding solution on vase life flowers. So Factorial Experiment was conducted by using Randomized Design with three replicate and three flowers for each. The results showed: plants of white flowers cultivars manifested the significant results in vase life, water uptake, change in fresh weight percent after 2 days and glucose concentration in flowers and stems at initial stage of vase life. Flowers pulsed in 5% sucrose gave significant higher values of vase life 11.5 days, water uptake 14.0 cm3, glucose concentration in flowers and stems at initial stage of vase life. Flowers treated with 300 mg/liter 8-HQS gave best results of vase life, higher percent increase in fresh weight after 2 days. In general, pulsing white cultivar flowers in 10% sucrose, then hold in 300 mg/liter 8-HQS manifested best result of vase life.